Importance of the Approach to Forensic Accounting in Reducing Financial Fraud: A Field Study on a Number of Auditing Offices and Judicial Courts Operating in Basra - Shibli , Abdulhussain Tofeeq; Salih , Jalil Ibrahim; Rahman, Nahla Ghalib Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Recently, there has been an increase in international interest in anti- financial fraud activities and their reduction, particularly in light of the technological advancement in the economic domain that makes it imperative for business organizations to fight financial fraud for survival. This is because financial fraud is the main cause for the collapse of many large companies such as, ENRON and WORLD.COM, and on this basis, accountants and auditors' interest has increased concerning the methods and mechanisms of discovering financial fraud issues. Correspondingly, there have been multiple accounting and auditing mechanisms brought forward to discover financial fraud, among which, forensic accounting is often utilized. This research aimed to identify the concept of forensic accounting approach, its significance and followed methods, to determine the role of a forensic accountant in reducing fraud and resolving many lawsuits to discover financial fraud. The study also identified the most prominent obstacles and difficulties that limit the application of forensic accounting to discover financial fraud. To achieve the goals of the study, a pilot study was conducted and 47 questionnaires were distributed, from which, 42 were retrieved, with a response rate of 89.36%. This is an acceptable result in terms of findings generalization to the population. The sample included a group of employees working in accounting and auditing offices and judicial courts in Basra. Among the most important results revealed in this research was that forensic accounting contributes in reducing fraud cases from judicial experts and legal accountants perspectives. In addition, results indicated difficulties and obstacles that deter the application of forensic accounting to discover fraud from the same perspectives.